Pendampingan Pembuatan Soal Ujian Berbasis Komputer dengan Aplikasi Wondershare Quiz Creator Bagi Guru di SMA Muhammadiyah Wonosari - Muhammad Sholeh; Untung Joko Basuki (Jurnal ABM Mengabdi, 2017)
The application of computer-based national examinations (UNBK) in schools must be balanced with the readiness of teachers in the learning process (PBM) in the classroom. In the process of doing test exercises, students must be familiarized in working on computer-based questions. In order for the process of doing the practice exam questions already using the computer, the teachers must first get used to preparing or making computer-based problems. One of the software that can be used in making computer-based problem is wonder share quiz creator. This app is devoted to making computer-based questions. In the process of making the question, the teacher can use the various features available in this application, such as randomisation of questions, responses or feedback from student answers and other features. Efforts to prepare teachers to get used to making computer-based test questions conducted in SMA Muhammadiyah Wonosari Gunung Kidul. In this assistance is given starting from the training process how to use quiz creator application, problem maker and distribution process of the question to the students.